2005
DOI: 10.2169/internalmedicine.44.590
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous Cystitis with Venous Bubbles

Abstract: An 86-year-old nondiabetic woman with an episode of transient ischemic attack two days earlier was referred to our hospital. She had a history of neurogenic bladder and chronic atrial fibrillation and had been anuric for two days. Bubbles were detected by echocardiography in the right atrium, right ventricle, and inferior vena cava. Computed tomography revealed gas accumulation in the wall and lumen of the bladder. She recovered after urinary drainage and antibiotic therapy, and bubbles were no longer detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
7
0
3
Order By: Relevance
“…In previous reports of EC with venous gas, due to suspected air embolism, one patient underwent a lung perfusion scan (7), whereas another underwent hyperbaric oxygen therapy as a preventative measure (6). Of the 15 cases in the present study, there were no cases of air embolism related to venous gas.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports of EC with venous gas, due to suspected air embolism, one patient underwent a lung perfusion scan (7), whereas another underwent hyperbaric oxygen therapy as a preventative measure (6). Of the 15 cases in the present study, there were no cases of air embolism related to venous gas.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial fermentation of glucose or albumin creates carbon dioxide gas bubbles, which collect in the submucosa or lumen of the bladder [9]. The risk factors of this disease include (i) advanced age, (ii) female gender, (iii) DM, (iv) neurogenic bladder, (v) urethral catheter placement, (vi) a vesicorectal fistula, (vii) end-stage renal disease, and (viii) outlet obstruction [10]. In the present case, the laboratory tests revealed that HbA1c was 7.3% with a serum glucose level of 525 mg/dL at the first visit.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial fermentation of glucose causes the formation of carbon dioxide gas bubbles (6,7). The risk factors of the disease include (i) advanced age, particularly for woman, (ii) diabetes mellitus, (iii) neurogenic bladder, (iv) urethral catheter placement, (v) vesicorectal fistula, (vi) end-stage renal disease, and (vii) outlet obstruction (8). The present case indicated three of these factors (advanced age, diabetes mellitus, and neurogenic bladder).…”
Section: Discussionmentioning
confidence: 99%